Calodioscurins A and B, two new isoprenylated xanthones from the stem bark of Calophyllum dioscurii P.F. Stevens - Tjitjik Srie Tjahjandarie*, . (Taylor & Francis, 2019)
Two new isoprenylated xanthones, calodioscurin A (1) and B (2) were isolated from the stem bark of Calophyllum dioscurii P.F. Stevens along with two known isoprenylated 4-phenylcoumarins, apetalolide (3) and methyl inophyllum P (4). The structures of two new compounds were determined based on their HRESIMS, IR, UV, 1D and 2D NMR spectral data. Compounds 1–4 were assayed on P-388 cells, compound 2 showed IC50 value 11.5 μM and categorised moderate activity.